Cyclisation of 1,2-dioxines containing tethered hydroxyl and carboxylic acid functionality: Synthesis of tetrahydrofurans and dihydrofuran-2(3H)-ones - Zvarec, O.; Avery, T.D.; Taylor, D.K.; Tiekink, E.R.T. (Elsevier, 2010)
Herein we outline cyclisations of tethered hydroxyl and carboxylic acid moieties onto the olefinic motif of 1,2-dioxines to generate tetrahydrofurans and dihydrofuran-2(3H)-ones, whilst maintaining the peroxide linkage intact. This work demonstrates the first examples of intramolecular cyclisation of tethered hydroxyl groupings onto 1,2-dioxines generating functionalised THFs in a highly stereoselective manner and includes improved methods for previously reported carboxylic acid tether cyclisations. Additionally, improved methods for the oxidation of 1,2-dioxines containing tethered alcohols to furnish tethered carboxylic acids are also detailed. Subsequent reduction of the peroxide linkage enables the generation of functionalised tetrahydrofurans and dihydrofuran-2(3H)-ones, which are useful building blocks for the construction of natural products. (C) 2009 Elsevier Ltd. All rights reserved.